Thermal conductivity of titanium aluminum silicon nitride coatings deposited by lateral rotating cathode arc - Ding, X. Z. (2013)
A series of physical vapour deposition titanium aluminum silicon nitride nanocomposite coating with a different (Al + Si)/Ti atomic ratio, with a thickness of around 2.5 μm were deposited on stainless steel substrate by a lateral rotating cathode arc process in a flowing nitrogen atmosphere. The composition and microstructure of the as-deposited coatings were analyzed by energy dispersive X-ray spectroscopy, and X-ray diffraction, and cross-sectional scanning electron microscopy observation. The titanium nitride (TiN) coating shows a clear columnar structure with a predominant (111) preferential orientation. With the incorporation of Al and Si, the crystallite size in the coatings decreased gradually, and the columnar structure and (111) preferred orientation disappeared. Thermal conductivity of the as-deposited coating samples at room temperature was measured by using pulsed photothermal reflectance technique. Thermal conductivity of the pure TiN coating is about 11.9 W/mK. With increasing the (Al + Si)/Ti atomic ratio, the coatings' thermal conductivity decreased monotonously. This reduction of thermal conductivity could be ascribed to the variation of coatings' microstructure, including the decrease of grain size and the resultant increase of grain boundaries, the disruption of columnar structure, and the reduced preferential orientation.